2004
DOI: 10.2320/matertrans.45.342
|View full text |Cite
|
Sign up to set email alerts
|

High-Cycle Fatigue Properties at Cryogenic Temperatures in INCONEL 718 Nickel-based Superalloy

Abstract: High-cycle fatigue properties at 4 K, 77 K and 293 K were investigated in forged-INCONEL 718 nickel-based superalloy with a mean gamma () grain size of 25 mm. In the present material, plate-like delta phase precipitated at grain boundaries and niobium (Nb)-enriched MC type carbides precipitated coarsely throughout the specimens. The 0.2% proof stress and the ultimate tensile strength of this alloy increased with decreasing temperature, without decreasing elongation or reduction of area. High-cycle fatigue stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 9 publications
2
17
0
2
Order By: Relevance
“…At lower stresses (<550 MPa), NT specimens have longer fatigue lifetimes, but the preyielded C sample shows the same fatigue behavior as the NT samples. Both NT and C samples exhibited a fatigue limit of approximately 445 MPa, which agrees with the findings of Ono et al [26] when a correction is made to their results to account for their fatigue testing condition of R = 0.01 versus R = -1, used here.…”
Section: G Uniaxial Tensile and High Cycle Fatigue Testingsupporting
confidence: 89%
“…At lower stresses (<550 MPa), NT specimens have longer fatigue lifetimes, but the preyielded C sample shows the same fatigue behavior as the NT samples. Both NT and C samples exhibited a fatigue limit of approximately 445 MPa, which agrees with the findings of Ono et al [26] when a correction is made to their results to account for their fatigue testing condition of R = 0.01 versus R = -1, used here.…”
Section: G Uniaxial Tensile and High Cycle Fatigue Testingsupporting
confidence: 89%
“…From the perspective of the fatigue source area as the fracture mode, the ST state had an obvious plastic fracture mode (Figures 5b and 7a), and the small facet of the cleavage for the fatigue fracture area of the ST + A state (Figure 6b,c) illustrated a cleavage fracture mode. Chen et al [10] showed that the fracture mode of the fatigue source area for an aged state Inconel 718 alloy changed from a transgranular ductile fracture to a cleavage fracture mode as the stress intensity factor k increased at the tip of the fatigue fracture. Accordingly, the k of the fatigue source area of the ST state was inferred to be smaller than that of the ST + A state.…”
Section: Analysis Of the High Cycle Fatigue Fracture Of The Inconel 7mentioning
confidence: 99%
“…Therefore, the research on fatigue performance of the Inconel 718 alloy has been widely concerned. According to the specific service environment temperature and load of the parts, it can be roughly divided into several aspects: high temperature [2]/medium temperature [3]/room temperature [4,5] low cycle fatigue, high temperature [6,7]/room temperature [8]/low temperature [9,10] high cycle fatigue, and ultra-high cycle fatigue [11,12] performance. Fournier et al [13] found that the Inconel 718 alloy in the solution treated and aged (ST + A) state had cyclic softening while in the direct aged (DA) state [14] had cyclic hardening under high temperature.…”
mentioning
confidence: 99%
“…It is desirable that the fatigue critical disks are produced with a fine grained microstructure in the range of 5-20 μm to maximize fatigue benefits. However, prior studies have shown that crack initiation at carbides is promoted at high stress amplitude [5] and also, at lower test temperatures [6], and therefore, the carbides might limit the benefits from grain refinement under certain conditions. Further, the carbides at the surface of the part are sensitive to damage from surface machining [7,8] or surface treatment processing, and in such cases, cracks may initiate early from carbides [9,10].…”
Section: Introductionmentioning
confidence: 99%